Teenage Pregnancy in Malang: The Analysis on Stunting Incidence in Toddler Aged 24-59 Months - Setyarini, Didien Ika; Triningsih, Reny Wahyu; Aryani, Hening Ryan (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Stunting is a chronic malnutrition problem characterized by short stature. Stunting toddlers are generally susceptible to disease, have a below normal level of intelligence and low productivity. The high prevalence of stunting in the long term will have an impact on economic losses for Indonesia, which one of the causes of it is early pregnancy. The aim of this study was to described teenage pregnancy with the incidence of stunting in 24-59 months toddlers. Subjects and Method: This research was a cross-sectional study. Sampling was carried out by a two-stage cluster sampling method using purposive sampling. 96 stunted toddlers were obtained. The dependent variable was mother's age at first pregnancy. The independent variable was stunting incidence. Data was collected using questionnaire data, body length, and weight measurements. Data were analyzed with descriptive analysis using SPSS Statististic 20. Results: 51.6% stunted toddlers were born by <20 years old mother at the time of first pregnancy. Almost all stunted toddlers were in the moderate stunting category (92.5%). 65.6% stunted toddlers didn’t get exclusive breastfeeding. 5.4% of 7.5% severe stunted toddlers were born by < 20 years old- mother at the time of first pregnancy. Conclusion: Pregnancy in teenager, when the mother herself is still growing, increases the risk of stunting. Stunting can also occur due to the lack of breastfeeding. It is necessary to make efforts to mature early marriage because it has an impact on unfavorable outcomes. Keywords: 24-59 months, pregnancy, stunting, teenage, and toddlers. Correspondence:Didien Ika Setyarini. Department of Midwifery, Poltekkes Kemenkes Malang. Jl. Besar Ijen No. 77C Malang 65119, East Java, Indonesia. Email:didien_ika@poltekkes-malang.ac.id. Mobile:08164- 296003